POTENSI LARVA IKAN DI PERAIRAN TELUK KOTANIA, KABUPATEN SERAM BAGIAN BARAT - Wadjo, Amirudin; Pello, Frederika S; Sahetapy, Dicky (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2023)
The presence of fish larvae is one of the main factors for the sustainability of fish resources. Information on the potential of fish larvae is very useful for the conservation of fish resources. This study aims to analyze species composition (richness), individual abundance, the relationship of fish larvae abundance with physical-chemical parameters and formulate strategies and priorities for fish larvae management. The research was conducted in August and October at 8 stations. Potential data were analyzed using diversity index, uniformity index, dominance, and abundance of fish larvae. PCA analysis was used to assess the relationship between water quality parameters and fish larvae abundance. SWOT and AHP analysis were used to formulate management strategies and priorities. Based on the results, 9 genus/species of fish larvae belonging to 9 families, 5 orders of Class Osteichtyes were obtained. The abundance of fish larvae was highest in October. Serranus sp. and Siganus sp. larvae had high individual abundance. The parameters salinity, water temperature, current speed, PO4, SiO3, pH, water brightness, and DO have a correlation (+), meaning that these water quality parameters had a directly proportional relationship with fish larvae abundance. Eight strategies were formulated, with two primary priorities for the potential development of fish larvae in Kotania Bay waters, three secondary priorities and three tertiary priorities. ABSTRAK Keberadaan larva ikan merupakan salah satu faktor utama kelestarian sumberdaya ikan. Informasi tentang potensi larva ikan sangat berguna bagi kelestarian sumberdaya ikan. Penelitian ini bertujuan untuk menganalisis komposisi (kekayaan) spesies, kelimpahan individu, hubungan kelimpahan larva ikan dengan parameter fisik-kimia dan merumuskan strategi serta prioritas pengelolaan larva ikan. Penelitian dilakukan pada Agustus dan Oktober di 8 stasiun. Analisa data potensi menggunakan indeks keanekaragaman, indeks keseragaman, dominansi, dan kelimpahan larva ikan. Analisis PCA digunakan untuk mengkaji hubungan parameter kualitas air dengan kelimpahan larva ikan. Analisis SWOT dan AHP digunakan untuk merumuskan strategi dan prioritas pengelolaan. Berdasarkan hasil penelitian diperoleh 9 genus/spesies larva ikan yang termasuk dalam 9 famili, 5 Ordo dari Class Osteichtyes. Kelimpahan larva ikan tertinggi pada bulan Oktober. Larva ikan Serranus sp. dan Siganus sp. memiliki kelimpahan individu tinggi. Parameter salinitas, suhu air, kecepatan arus, PO4, SiO3, pH, kecerahan air, dan DO memiliki korelasi (+), yang berarti parameter kualitas perairan itu memiliki hubungan berbanding lurus dengan kelimpahan larva ikan. Dirumuskan delapan strategi, dengan dua prioritas primer pengembangan potensi larva ikan di perairan Teluk Kotania, tiga prioritas sekunder dan tiga prioritas tersier. Kata Kunci: komposisi, kelimpahan, larva ikan, pengelolaan, Teluk Kotania